Ragam Komunikasi Verbal dalam Al-Qur’an - Subhan Afifi; Irwan Nuryana Kurniawan (Jurnal Komunikasi)
Abstract. This paper attempts to trace various forms of verbal communication in the Qur'an. This study uses descriptive qualitative research design. Data for this study were collected using library research methods and in-depth interviews. Library Research is carried out by studying various Qur'anic commentaries related to the principles and types of verbal communication. In-depth interviews were conducted with scholars who were competent in the field of Al-Qur'an exegesis and preachers / Al-Qur'an teachers who had preaching experience in the community. The research findings show several kinds of verbal communication found in Al-Qur'an, namely: Qaulan Sadidan, Qaulan Ma'rufan, Qaulan Maysuran, Qaulan Kariman, Qaulan Balighan, and Qaulan Layyinan. Each of these types of verbal communication has a specific concept, context, and explanation.